Fast Brain Plasticity during Word Learning in Musically-Trained Children - Dittinger, Eva; Chobert, Julie; Ziegler, Johannes C.; Besson, Mireille (Frontiers in Human Neuroscience, 2017)
Children learn new words every day and this ability requires auditory perception, phoneme discrimination, attention, associative learning, and semantic memory. Based on previous results showing that some of these functions are enhanced by music training, we investigated learning of novel words through picture-word associations in musically-trained and control children (8-12 year-old) to determine whether music training would positively influence word learning. Results showed that musically-trained children outperformed controls in a learning paradigm that included picture-sound matching and semantic associations. Moreover, the differences between unexpected and expected learned words, as reflected by the N200 and N400 effects, were larger in children with music training compared to controls after only 3 minutes of learning the meaning of novel words. In line with previous results in adults, these findings clearly demonstrate a correlation between music training and better word learning. It is argued that these benefits reflect both bottom-up and top-down influences. The present learning paradigm might provide a useful dynamic diagnostic tool to determine which perceptive and cognitive functions are impaired in children with learning difficulties.